Pregnancy after liver transplant: maternal and perinatal outcomes - Izabela Marzec; Aleksandra Słowakiewicz; Jolanta Gozdowska; Olga Tronina; Marek Pacholczyk; Wojciech Lisik; Agata Fleming; Magdalena Durlik (BMC, 2021)
Abstract Background Liver transplantation is a life-saving and successful therapeutic procedure which is more and more frequent worldwide, also among women of reproductive age. Consequently, there is an increasing number of reports of pregnancy following liver transplantation, but doubts still exist regarding preconception counseling and the optimal method of managing pregnancy. The aim of this study was to report and evaluate pregnancy outcomes in women who had undergone liver transplantation. Methods We retrospectively analyzed female patients after orthotopic liver transplantation who reported pregnancy and were under medical care of a single transplant center. Results We identified 14 pregnancies in 10 women who had undergone liver transplantation (12 childbirths, one induced abortion due to fetal death in the first trimester, one pregnancy is still ongoing). Causes of transplantation include congenital or acquired disorders and the most common indication was autoimmune hepatitis (50%). The mean age at the point of transplantation was 28.5 (range 21-36), mean maternal age at pregnancy was 32 (range 26-43), and transplant-to-pregnancy interval was 4.07 years (range 1.5-7). The mean gestational week was 36.67 (range 31-40). Immunosuppression was maintained with combinations of prednisone (n = 11), tacrolimus (n = 13), and azathioprine (n = 8) prior to and during pregnancy. Two pregnancies were unintended, so women took mycophenolate mofetil in the first weeks of gestation. Another two women stopped taking azathioprine due to increasing anemia. Maternal complications included increase of aspartate transaminase and alanine transaminase (n = 2), anemia (n = 4) and hyperthyroidism (n = 2). Among the 12 childbirths, five (41.67%) were preterm. Only five women entered labor spontaneously, while seven (58,33%) had cesarean delivery. Conclusions Pregnancy after liver transplantation can achieve relatively favorable outcomes. Liver transplantation does not influence women's fertility and, during pregnancy, we report low rates of minor graft complications. A multidisciplinary team should be involved in contraceptive, fertility and consequently pregnancy counseling of female transplant recipients.